2022
DOI: 10.22334/traverse.v3i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Identify the types & reason of code mixing found in whatsapp group cargo department staff at ngurah rai airport

Abstract: The aims of this study are to find out (1) the types of code mixing found in WhatsApp Group cargo department by the staffs at Ngurah Rai Airport and (2) to analyse the reason of code mixing found in the WhatsApp Group by the staff at Ngurah Rai Airport. The data were taken from chat of cargo department staff in WhatsApp Group at Ngurah Rai Airport. The method of collecting data was starting from March 1 to 30, 2021. The analysis was done by applying descriptive qualitative method requires documentation to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The second theory applied from Holmes (2013) to explain the reasons of code switching. The study by Muttaqien, et al (2022) found only two types of code mixing such as; intra-sentential code mixing and intra-lexical code mixing. That study found four reasons of code mixing, such as; topic, participant, solidarity, and status.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The second theory applied from Holmes (2013) to explain the reasons of code switching. The study by Muttaqien, et al (2022) found only two types of code mixing such as; intra-sentential code mixing and intra-lexical code mixing. That study found four reasons of code mixing, such as; topic, participant, solidarity, and status.…”
Section: Introductionmentioning
confidence: 96%
“…According to the study's findings, there are three different types of code switching on Cinta Laura's Instagram account, with intra-sentential switching being the most common type and specific topic the most common cause. While the second study written by Muttaqien, Sulatra, Jendra (2022) analysed the types and reason of code mixing and used WhatsApp as the data source. The data were analysed based on Hoffman's (1991) to explain the types of code switching.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it occurs when a speaker whose mother tongue is Indonesian speaks this language and inserts a word or some words from another language, such as English, in his/her sentences. It seems that the use of code-mixing is rarely realized by users (Muttaqien et al, 2022). Nowadays, inserting English into Indonesian conversation is considered very common.…”
Section: Introductionmentioning
confidence: 99%